Application of Decision Support System and Business Intelligence Model for Identification and Determination of Stunting - Salahuddin; M.Reza Zulman; Radhiyatammardhiyyah; Nurmila Dewi (Jurnal Serambi Engineering, 2024)
It is imperative to identify stunting in toddlers at an earlier stage in order to facilitate further treatment related to the health of toddlers, with the ultimate goal of improving the health status of toddlers. Stunting problems are not only related to health problems. The purpose of this study is to design and build DSS intelligence applications for the purpose of identifying stunting and determining stunting status in toddlers using Promethee models. It is anticipated that the DSS application will facilitate the early detection of stunting in toddlers and assist the Lhokseumawe City Health Office in determining the status of stunting in toddlers. The research methodology comprises a series of stages, commencing with a literature review and data collection, followed by the identification of the requirements for DSS applications, the design of the DSS application, the coding of the DSS application and the testing of the DSS applications. In this study, 27 test data (alternatives) were selected, each of which met six criteria. These criteria were age, weight, height, head circumference, speech style and behaviour. The results of the DSS system testing indicated that eight toddlers were identified as stunted, with net flow values between 0.54691588785047 and 0.65308411214953. Conversely, 19 children under five were classified as non-stunted, with net flow values below 0.5.